Hybridity and the Space of the Border in the Writing of Norma Elia Cantú - Ellen McCracken (Studies in 20th & 21st Century Literature, 2001)
The creative and scholarly writing of Norma Elia Cantú focuses centrally on the tensions of borders that are eroding yet firmly in place. Cantú's border pivots on the geographic space in which Mexico and the United States physically intersect, yet she probes at the same time several of the other tenuous cultural borders that postmodernity has brought into focus. Transcending distinctions between genres, languages, and cultures, Cantú undertakes innovative genre hybridity, visual-verbal hybridity, and the recombination of distinct cultural codes. Whether writing cultural criticism, autobioethnography, creative fiction, or poetry, Cantú locates herself at the intersection of the geographical and epistemological borders central to postmodernity.
Keywords: space; border space; border narrative; hybridity; Norma Elia Cantú; scholarly writing; creative writing; border tension; conflict; Mexico; U.S.; cultural borders; culture; identity; language; genre hybridity; culture code; epistemological border; postmodernity